The use of Social Network Sites (SNSs) among lecturers at the higher education - Landani, Zahra Mardani; Syed Hassan, Sharifah Sariah (Amazon, 2015)
The advancement of mobile technology has changed the traditional communication and teaching to novel teaching and learning. Communication through social network sites (SNSs) has given a new trend in teaching and learning. The purpose of this book is to summarize the influence of the teaching strategies via Social Network Sites (SNSs)on Students'satisfaction.The target is students, lecturers, and researchers who are interested in SNSs in the field of instructional technology.